Author Correction: Covalent coupling of Spike’s receptor binding domain to a multimeric carrier produces a high immune response against SARS-CoV-2 (Scientific Reports, (2022), 12, 1, (692), 10.1038/s41598-021-03675-0) - Berguer, Paula Mercedes (2022)
The original version of this Article contained an error in Figure 7 where a preliminary rendition was published. The original Figure 7 and accompanying legend appear below. The original Article has been corrected.